STRATEGI PENGUATAN KEWIRAUSAHAAN UNTUK MENINGKATKAN KINERJA USAHA (Survey pada Wirausaha Fesyen di BTC dan PGS Surakarta) - Retno Susanti; Suprihatmi SW (Universitas Slamet Riyadi, 2020)
The creative economy of the fashion business in BTC and PGS Surakarta is very important to be developed because it contributes to the regional economy. Constraints faced in running a business such as entrepreneurship orientation is low, so that the business performance is not optimal. One strategy to encourage the development of creative economy in the business of fashion in Surakarta is to increase creativity and market orientation, in order to obtain maximum business performance. This study aims to analyze the effect of entrepreneurship orientation on business performance moderated by creativity and market orientation. Sample of this study are 123 entrepreneurs of fashion in BYC and PGS Surakarta, using purposive sampling technique. Data analysis using regression analysis and Absolute Difference Test. The conclusion of hypothesis test result (1) entrepreneurship orientation have significant effect on business performance; (2) creativity can moderate the effect of entrepreneurship orientation on business performance; (3) market orientation can moderate the effect of entrepreneurship orientation on business performanceKeywords: entrepreneurship orientation, creativity, market orientation, business performance